Impact of back-contact materials on performance and stability of CdS/CdTe solar cells - Demtsu, Samuel H., author; Sites, James R., advisor; Patton, Carl, committee member; Leisure, Robert, committee member; Sampath, W. S., committee member (Colorado State University. Libraries, 2006)
Thin-film CdTe based solar cells are one of the leading contenders for providing low-cost and pollution-free energy. The formation of a stable, low resistance, non-rectifying contact to p-CdTe thin-film is one of the major and critical challenges associated with this technology in the fabrication of efficient and stable solar cells. The premise of this thesis is a systematic study of the impact of back-contact materials on the initial performance and the degradation of CdS/CdTe solar cells. Two different back-contact structures that incorporate Cu as a key element are investigated in this study: (a) Cu1.4 Te:HgTe-doped graphite and (b) evaporated-Cu back contacts. The effect of Cu inclusion is not limited to the back-contact layer where it is deposited. Cu is a known fast diffuser in p-CdTe, and therefore, a significant amount of Cu reaches both the CdTe and CdS layers. Hence, the effect of the presence of Cu on the individual layers: back-contact, the absorber (CdTe), and the window (CdS) layers is discussed respectively. The effect of different metals used to form the current-carrying electrode following the Cu layer is also evaluated. Devices are studied through current-voltage (JV) measurements at different temperatures and intensities, quantum efficiency (QE) measurements under light and voltage bias, capacitance-voltage (CV), drive-level-capacitance-profiling (DLCP), and time-resolved photoluminescence (TRPL) measurements. Numerical simulation is also used to reproduce and explain some of the experimental results. In devices made without Cu, a current-limiting effect, rollover (distortion) in the current-voltage characteristic, was observed. With the inclusion of a small amount of Cu (5-nm), however, the distortion disappeared, and higher FF was obtained. The performance of these devices was comparable to devices made with the standard Cu-doped graphite paste contacts when the same CdTe absorber is used. Small amount of Cu (5-20 nm) partially diffused into the CdTe absorber layer resulted in increased hole density, and improved Voc. However, excess Cu (100 nm) created recombination centers that significantly reduced the FF and Voc. The presence of Cu in the CdS window layer had minimal effect on device performance. It was found, however, to be responsible for anomalies such as dark/light crossover and distortions in apparent quantum efficiency, neither of which has a direct impact on the device performance. Numerous metals: Au, Cr, Pd, Pt, and Ni were evaporated, following the Cu layer, and were found to form good current-carrying electrodes. Ag and Al, however, did not perform well in this role. With exposure to elevated temperature (60-120°C) for extended period of time, diffusion of Cu from the back contact was found to cause back-contact degradation and additional increases in CdTe recombination. This degradation resulted in a reduced fill-factor, due to the formation of the Cu-depleted blocking contact and the consequent reduction in collection efficiency.
Impact of back-contact materials on performance and stability of cadmium sulfide/cadmium telluride solar cells
Keywords: condensation; energy; condensed matter physics